The Effectiveness of Juvenile Diversion in Indonesia, Malaysia, and the Philippines: A Comparative Study of ASEAN Justice Systems - Kossay, Methodius; Dalimunteh, Nur Amannah; Sitompul, Abdul Romadon (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The diversion system provides an alternative approach to resolving cases involving children in conflict with the law (CICL), while upholding the values of restorative justice and social reintegration. This study compares the effectiveness of diversion systems in Indonesia, Malaysia, and the Philippines by examining the laws, implementation practices, and outcomes of their application. In a qualitative-comparative approach, data were obtained through in-depth interviews with 30 key informants, document analysis, and limited observation. Research findings indicate that Indonesia and Malaysia exhibited near-comparable effectiveness levels (with an average score of 3.5 within a 1-5 scale), whereby regulatory frameworks and recidivism prevention appeared as Indonesia's strengths, and social reintegration in the community was better in Malaysia. However, contrary to a sound legal framework, the Philippines was ranked the least effective (score of 2.25), particularly due to the lack of necessary institutional capacities. This research presents a comprehensive, cross-jurisdictional evaluation framework that emphasizes the integration of legal and social processes within juvenile justice systems. The findings create a strategic basis for formulating more responsive, child-centered policies and assist with the harmonization of child protection systems across the ASEAN region.